An Unusual Carbon–Ceramic Composite with Gradients in Composition and Porosity Delivering Outstanding Thermal Protection Performance up to 1900 °C. (6th July 2022) - Yan, Meng; Hu, Chenglong; Li, Jian; Zhao, Rida; Pang, Shengyang; Liang, Bin; Tang, Sufang; Liu, Gang; Cheng, Hui–Ming
Abstract: Developing materials that do not ablate, which are thermally insulating and strong at temperatures above 1650 °C, is of prime importance for the thermal protection of aerospace vehicles, but remains a great challenge. Carbon aerogels (CAs) are attractive candidates for thermal protection due to their excellent thermostability and thermal insulation. However, their poor anti‐oxidative performance and difficulty in producing an anti‐oxidative refractory coating, as well as brittleness and low mechanical strength severely limit their practical use, especially in oxidizing environments. Here, an unusual carbon fiber‐reinforced carbon–ceramic composite with gradual changes in composition and pore size is reported. On the top is a carbon fiber‐reinforced SiCC modified by mullite‐Al2 O3 and at the bottom is a carbon fiber‐reinforced analogous CA. The resulting material shows excellent ablation resistance, outstanding thermal insulation, extremely high thermostability, and strong load‐carrying capacity. Compared with conventional porous non‐ablative and thermal insulating materials with a working temperature of 1600 °C and a specific strength of 10 MPa g –1 cm –3, its respective values are increased to 1900 °C and 119 MPa g –1 cm –3 . This work provides a new way to improve the ablation resistance property of nano‐porous carbon monoliths, and the carbon‐ceramic composite developed has great promise for ultra‐high temperature thermal protection in aerospace. Abstract : Here, an unusual carbon fiber‐reinforced carbon–ceramic composite with gradients in composition and pore size is reported. On the top is a carbon fiber‐reinforced SiCC modified by mullite‐Al2 O3 and at the bottom is a carbon fiber‐reinforced analogous CA. The composite shows excellent ablation resistance, outstanding thermal insulation, extremely high thermostability, and strong load‐carrying capacity at 1900 °C.